Genome : the autobiography of a species in 23 chapters - Ridley, Matt. (New York : HarperCollins, 1999)
The author examines some of the findings of the Human Genome Project, telling the story of one newly discovered gene from each of the twenty-three human chromosomes, and discussing what those genes reveal about the history of the human species.
Includes bibliographical references (p. 314-336) index.
Library Journal.
Notable/Best Books (A.L.A.).
Wilson's Senior High School.
Adult.
Adult
Keywords: Human genetics -- Popular works; Human genome -- Popular works; Genetics